Analisis Perbaikan Sistem Kerja pada Proses Produksi Kultur Jaringan Kelapa Sawit dengan Mengunakan RULAdan REBA di PT XYZ - Kurniasih, Nia; Ahmad F, wakhit; Zulziar, Marjuki (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
Work comfort is an important factor in the production process, as it can reduce complaints from workers, especially for handling staff. One of the issues arising from insufficient comfort and safety in the workplace is Musculoskeletal Disorders (MSDs). This study aims to analyze the workers' posture and improve the work system in the oil palm tissue culture production process, using the Rapid Upper Limb Assessment (RULA) method to reduce the risk of MSDs. Based on data from 2022, workers experienced complaints with an average score of 21.92 and a severity level of 13%. This study focuses on evaluating workers' posture during the selection of oil palm shoots and measuring work posture scores using the Nordic Body Maps (NBM) and RULA methods. The analysis showed that 26% of workers experienced pain in every workflow, which needs improvement, with the upper body being the most affected. RULA scores indicated that several operators fell into the high-risk category, with scores ranging from 5 to 7, signaling the need for improvement. As a corrective measure, this study suggests adding portable ladder tools to improve comfort and accessibility for workers, particularly for operators with a height of 145-165 cm and a weight of 50-65 kg. The addition of portable ladders is expected to reduce work strain and minimize the risk of injury for workers. Keywords: Posture Improvement, NBM, RULA.